Lycorine hydrochloride interferes with energy metabolism to inhibit chemoresistant glioblastoma multiforme cell growth through suppressing PDK3 - Qingsheng Dong; Wanxiang Niu; Maolin Mu; Chengkun Ye; Pengfei Wu; Shanshan Hu; Chaoshi Niu (Molecular and Cellular Biochemistry, 2025)

Suppressing leakage current and charge accumulation via perovskite interface morphology regulation for efficient light-emitting diodes - Yongjian Chen; Xiankan Zeng; Cheng Yan; Shiyu Yang; Lunyao Pan; Chenglong Li; Maolin Mu; Wen Li; Guanqi Tang; Weiqing Yang (Chemical Engineering Journal, 2024)

Exosomal circZNF800 Derived from Glioma Stem-like Cells Regulates Glioblastoma Tumorigenicity via the PIEZO1/Akt Axis - Ning Zhang; Pengfei Wu; Maolin Mu; Chaoshi Niu; Shanshan Hu (Molecular Neurobiology, 2024)
Exosomes play a crucial role in regulating crosstalk between tumor and tumor stem-like cells through their cargo molecules. Circular RNAs (circRNAs) have recently been demonstrated to be critical factors in tumorigenesis. This study focuses on the molecular mechanism by which circRNAs from glioma stem-like cell (GSLC) exosomes regulate glioblastoma (GBM) tumorigenicity. In this study, we validated that GSLC exosomes accelerated the malignant phenotype of GBM. Subsequently, we found that circZNF800 was highly expressed in GSLC exosomes and was negatively associated with GBM patients. CircZNF800 promoted GBM cell proliferation and migration and inhibited GBM cell apoptosis in vitro. Silencing circZNF800 could improve the GBM xenograft model survival rate. Mechanistic studies revealed that circZNF800 activated the PIEZO1/Akt signaling pathway by sponging miR-139-5p. CircZNF800 derived from GSLC exosomes promoted GBM cell tumorigenicity and predicted poor prognosis in GBM patients. CircZNF800 has the potential to serve as a promising target for further therapeutic exploration.